Object Movement Detection System Using GPS, Passive Infrared Sensor, and Ultrasonic Sensor for Military Training Applications: Telekomunikasi Militer - Yedhi Oktafianto; Gatut Yulisusianto; Vincensius Arga Yoda (Pustaka Poltekad, 2026)
Area security and movement control play a critical role in military training operations, particularly in tactical exercises conducted within restricted and predefined zones. Effective detection and monitoring of troop movement are required to ensure training safety, operational realism, and accurate situational awareness. Inadequate or delayed detection may lead to training disruption, reduced effectiveness, and potential safety risks. This paper proposes an integrated object movement detection system based on a microcontroller platform, utilizing a Passive Infrared (PIR) sensor, an ultrasonic sensor, and a Global Positioning System (GPS) module to implement a multi-level early warning mechanism for military training applications. The PIR sensor is employed to detect human motion through infrared radiation changes, while the ultrasonic sensor measures object distance using ultrasonic wave propagation to identify critical proximity thresholds. The GPS module enables real-time tracking of troop positions, with collected data transmitted wirelessly to a centralized monitoring server for remote supervision. The proposed system generates staged alerts, including an initial warning upon movement detection and a secondary warning when the object enters a predefined critical zone, delivered via audio indicators and telemetry-based notifications. Experimental evaluation conducted under simulated training scenarios demonstrates that the system is capable of accurately detecting movement, providing reliable distance measurement, and supporting real-time location monitoring with acceptable response time and stability. The results indicate that the proposed system enhances training safety and control, offering a modular and scalable solution suitable for the development of advanced sensor-based early warning and monitoring systems in military training environments.